Cultural and Religious Values in Shaping Future Taxpayer Compliance: Nilai Budaya dan Religiusitas dalam Membentuk Kepatuhan Calon Wajib Pajak - Wardani, Dewi Kusuma; Azizah, Mega (Universitas Muhammadiyah Sidoarjo, 2025)
General background: Tax compliance plays a critical role in sustaining national development, yet individual compliance remains relatively low in Indonesia. Specific background: Previous studies largely emphasize technical or regulatory factors, while limited attention is given to cultural and spiritual values. Knowledge gap: Few studies explore the integration of Ki Hadjar Dewantara’s Tri N teachings with religiosity in explaining prospective taxpayers’ compliance. Aims: This study investigates how understanding the Tri N values (niteni, niroake, nambahi) and religiosity contribute to compliance intentions among accounting students. Results: Using a quantitative approach with 100 respondents and multiple regression analysis, findings show both Tri N understanding and religiosity significantly predict compliance, with religiosity showing a stronger coefficient. Novelty: This study offers a unique cultural-spiritual integration within behavioral taxation, highlighting that Tri N values support moral and character development while religiosity provides stronger internalized motivation for compliance. Implications: The findings suggest that tax education programs should incorporate local cultural wisdom and religious values to foster voluntary compliance among young taxpayers, strengthening fiscal trust and long-term sustainability. Highlight Tri N values and religiosity significantly predict taxpayer compliance Religiusitas exerts stronger influence than cultural values Education programs should integrate local wisdom with fiscal policy Keywords Tri N Values, Religiosity, Tax Compliance, Cultural Wisdom, Behavioral Taxation